Fretting Wear and Fatigue Life Analysis of Fuel Bundles Subjected to Turbulent Axial Flow in CEFR - Yafeng Shu; Jianjun Wu; Yongwei Yang; Zelong Zhao (Science and Technology of Nuclear Installations)
In a fast spectrum reactor, the fuel rod bundle is mainly positioned radially by the wire which can make contact with the adjacent fuel rods, and then it is inevitable that flow-induced vibration (FIV) will cause fretting wear and vibration fatigue of the fuel cladding at the contact position. Therefore, the computational model of fretting wear and fatigue life about the fuel rod bundle caused by FIV will be studied in this paper. Based on the random vibration model of the fuel rod bundle, Hertz contact theory, and Archard wear theory, the fretting wear life computational model and the fatigue life computational model of the wire-to-adjacent fuel rod (WAFR) contact have been established. Finally, taking CEFR design parameters as an example, the fretting wear life and vibration fatigue life of the cladding are calculated, and it is found that fatigue affects the service life of the fuel rod more seriously than fretting wear. The calculation model and method lay a foundation for further accurate prediction and analysis of the fuel rod life.